Role of the Gut Microbiome in Obesity and Diabetes Mellitus. (9th October 2015) - Barlow, Gillian M.; Yu, Allen; Mathur, Ruchi
Abstract : Type 2 diabetes mellitus (T2DM) and obesity represent two of the biggest global health challenges of this century and are associated with significant comorbidities and healthcare costs. Although multiple factors undoubtedly contribute to the development and progression of DM and obesity, research over the last decade has demonstrated that the microbes that colonize the human gut may play key contributory roles. Gut microbes are now known to codevelop with the human host and are strongly influenced by mode of birth and early diet and nutrition, as well as environmental and other factors including antibiotic exposure. Gut microbes contribute to human health through roles in polysaccharide breakdown, nutrient absorption, inflammatory responses, gut permeability, and bile acid modification. Numerous studies have suggested that disruptions in the relative proportions of gut microbial populations may contribute to weight gain and insulin resistance, including alterations in Gammaproteobacteria and Verrucomicrobia and the ratios of Firmicutes to Bacteroidetes in weight gain and possible alterations in butyrate‐producing bacteria such as Faecalibacterium prausnitzii in DM. In addition, it has been shown that the methanogenic Archaea may contribute to altered metabolism and weight gain in the host. However, the majority of studies are performed with stool or colonic samples and may not be representative of the metabolically active small intestine. Studies predominantly in rodent models are beginning to elucidate the mechanisms by which gut microbes contribute to DM and obesity, but much remains to be learned before we can begin to approach targeted treatments.